Kalibrasi Satu Dan Dua Parameter Pada Debit Banjir Di Sub-DAS Rokan Menggunakan Program HEC-HMS - Permatasari, Yesy Dian; Handayani, Yohanna Lilis; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Floods occurred in Rokan Hulu are due to heavy rainfall with fairly long duration and high rainfall. The main difficulty encountered in the analysis of river flooding in Rokan Hulu is due to limited availability of data. An alternative to overcome these limitations is to use a hydrological model. In this research was used as a calibration adjustment process model parameter values to obtain a result of the same model or close observation. This study aims to look at the characteristics of the calibration using rainfall data and flow data hourly to the Transform Method Clark Unit hydrograph and Transform Method Snyder Unit Hydrograph, by using hydrologic Engineering Center Modeling System (HEC-HMS). The best result of the calibration is to use two parameters, the results of two-parameter calibration method Transform Method Clark unit hydrograph has the result Different Percent Percent Peak = 0.0 and Different Volume = -7.67 and methods Transform Method Snyder unit hydrograph have results Different Percent Peak = 0.0 and Different Percent Volume = -23.43. From the results of the calibration is the best method is Transform Method Clark Unit Hydrograph.Keywords: DAS, debit, HEC-HMS